Thermal stability of the nanocrystalline Fe-8P (wt.%) powder produced by ball milling. (3rd August 2018) - Tebib, Wassila; Alleg, Safia; Grenèche, Jean-Marc; Suñol, Juan Jose
GRAPHICAL ABSTRACT: ABSTRACT: The thermal stability of Fe-8P (wt.%) ball milled powders was investigated by differential scanning calorimetry X-ray diffraction and 57 Fe Mössbauer spectrometry. The effect of structural disorder is evidenced in the DSC thermogram by the presence of a large exothermic reaction consists of several overlapping peaks and spread over the temperature range (150-700)°C. The result of the Rietveld refinement of the XRD patterns indicates that during the annealing of the powders up to 210°C, three phases are observed: α-Fe(P), solid solution Fe3 P and FeP phosphides. The Mössbauer spectra analyses show that the paramagnetic FeP phosphide phase is the only product after the annealing (∼ 2%). The annealing at 450°C leads to a mixture of α-Fe(P) solid solution, Fe3P nanophase and a small amount of a paramagnetic FexP (1 < x < 2) phosphide phase (∼ 3%) in addition to iron oxides.